Mitos dan Eksplanasi Ilmiah Lembayung Senja - Rahmat Rizal (Jurnal Filsafat Indonesia, 2018)
A Violaceous sky attwilightis a natural phenomenon that occurs at sunset. This phenomenon is characterized by areddish yellow sky appearance. To explain this phenomenon, the community has developed a myth that connects the existence of the occult things such as the decline of the evil ghosts, witchcraft, and the epidemic of the disease. This myth has survived long enough in both sundanesse and Banjarmasin, South Kalimantan. The myth is spread in the community from mouth to mouth and occurs from generation to generation. Development of science and the changing minds of modern society effect myths that are present in society began to be degraded by scientific explanations reinforced by empirical evidences. The explanation used in explaining the twilight phenomenon uses the Hempel-Oppenheim explanation model. The explanationsare considered as general statementsconsidered correct. The Violaceous sky at twilight does not indicate the presence of ghosts, witches, or epidemics but it can be explained by Rayleigh scattering theory. The white light from the sun is dissipated by the atmospheric particles into the monochromatic spectrum. As a result of longer stages, the scattered spectrum has the longest wavelength